Roles of E. coli double-strand-break-repair proteins in stress-induced mutation - He, Albert S. (2005)
Special mechanisms of mutation are induced during growth-limiting stress and can generate adaptive mutations that permit growth. These mechanisms may provide improved models for mutagenesis in antibiotic resistance, evolution of pathogens, cancer progression and chemotherapy resistance. Stress-induced reversion of an Escherichia coli episomal lac frameshift allele specifically requires DNA double-strand-break-repair (DSBR) proteins, the SOS DNA-damage response and its error-prone DNA polymerase, DinB. We distinguished two possible roles for the DSBR proteins. Each might act solely upstream of SOS, to create single-strand DNA that induces SOS. This could upregulate DinB and enhance mutation globally. Or any or all of them might function other than or in addition to SOS promotion, for example, directly in error-prone DSBR. We report that in cells with SOS genes derepressed constitutively, RecA, RuvA, RuvB, RuvC, RecF and TraI remain required for stress-induced mutation, demonstrating that these proteins act other than via SOS induction. RecA and TraI also act by promoting SOS. These and additional results with hyper-mutating recD and recG mutants support roles for these proteins via error-prone DSBR. Such mechanisms could localize stress-induced mutagenesis to small genomic regions, a potentially important strategy for adaptive evolution, both for reducing additional deleterious mutations in rare adaptive mutants and for concerted evolution of genes.